2001
DOI: 10.1093/emboj/20.22.6414
|View full text |Cite
|
Sign up to set email alerts
|

Activation of MEF2 by muscle activity is mediated through a calcineurin-dependent pathway

Abstract: Gene expression in skeletal muscles of adult vertebrates is altered profoundly by changing patterns of contractile work. Here we observed that the functional activity of MEF2 transcription factors is stimulated by sustained periods of endurance exercise or motor nerve pacing, as assessed by expression in transgenic mice of a MEF2-dependent reporter gene (desMEF2-lacZ). This response is accompanied by transformation of specialized myo®ber subtypes, and is blocked either by cyclosporin A, a speci®c chemical inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
294
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 324 publications
(315 citation statements)
references
References 50 publications
(75 reference statements)
20
294
1
Order By: Relevance
“…This latter observation suggests that cold exposure influences fiber phenotype via signals other than PGC-1a. In this regard, the fiber type conversion shown here is similar to what has been observed with calcineurin [31] and PGC-1a [2], transgenics and exercise [32]. The results of the Northern blot analysis revealed that avUCP and avANT transcript levels concomitantly increased from days 1 to 2, and then decreased slightly over the next 5 days, but remained higher than control values ( Fig.…”
Section: Discussionsupporting
confidence: 87%
“…This latter observation suggests that cold exposure influences fiber phenotype via signals other than PGC-1a. In this regard, the fiber type conversion shown here is similar to what has been observed with calcineurin [31] and PGC-1a [2], transgenics and exercise [32]. The results of the Northern blot analysis revealed that avUCP and avANT transcript levels concomitantly increased from days 1 to 2, and then decreased slightly over the next 5 days, but remained higher than control values ( Fig.…”
Section: Discussionsupporting
confidence: 87%
“…It was suggested that transcriptional activation of PGC-1␣-a is induced by the interaction on the MEF2 binding site and CRE sequences on the PGC-1␣-a promoter with regulatory factors such as MEF2, class IIa histone deacetylases (HDACs), ATF2, and CREB (1). AMPK, CaMK, CnA, and p38 MAPK have been reported to modulate these regulatory factors (2,7,9,22,29,34,35,38,44). Modulation of these transcription factors and the regulators by these protein kinases and phosphatase might be involved in high-intensity exercise-induced PGC-1␣-a expression.…”
Section: E346 Effects Of Exercise and Aicar On Pgc-1␣ Isoformsmentioning
confidence: 99%
“…Calcineurin up-regulates the transcription of MEF2 genes (Wu et al, 2000a). It can also dephosphorylate MEF2 directly and enhance its transactivational activity (Dunn et al, 2001;Wu et al, 2001). Hence members of the MEF2 family are transcriptional targets and protein substrates of calcineurin.…”
Section: Fibre Types: Coordinated Isoform-specific Expressionmentioning
confidence: 99%